PSIII-7 Determining the requirement of puberty induction to the reproductive performance of Bos indicus-influenced heifers submitted to AI. (30th November 2020) - Martins, Thiago; da Silva, Felipe A C C; Sponchiado, Mariana; Soriano, Gabriela A; Pinto, Leonardo M F; Rocha, Cecilia C; Podversich, Federico; Tarnosky, Federico; Lenin, Yasser; Driver, Joseph D; David, Thomas; Rae, Owen; et al.
Abstract: Induction of puberty by treating heifers with progesterone (P4) inserts may favor pregnancy/AI (P/AI) to a subsequent estrus synchronization program. However, it remains to be elucidated whether induction is required when the synchronization program contains P4 supplementation. To address this question, yearling, Brahman-influenced heifers (mostly 3/8 Brahman) classified as pubertal (PUB; n = 363) or prepubertal (PRE; n = 214) based on the presence of a CL, were assigned to receive no P4 supplementation (NoCIDR) or a CIDR for 10 days, starting on D-23. On D-13, all heifers received a dose of prostaglandin analogue and CIDRs were removed. On D-9, all heifers were enrolled in a 6-day CIDR & TAI protocol. Heifers were serviced based on heat between D-2 and D0 or were TAI on D0. Reproductive tract scores (RTS, 1 to 5 scale) were evaluated on D-23 and D-3. Induction increased the proportion of PRE heifers bearing a CL on D-3 (PRE|CIDR: 60.3% vs. PRE|NoCIDR: 42.7%). Among heifers with CL on D-3, P/AI of PRE heifers (42.5%) was similar to that PUB (47.7%). Conversely, for heifers without CL on D-3, P/AI of PRE (14.7%) was lower than PUB (37.3%). RTS increased between D-23 and D-3 from 2.3 to 4.0 (CIDR) and 2.3 to 3.6 (NoCIDR). For every 1-point increase in RTS, P/AI was 6–9% greater. Despite hastened puberty, P/AI of PRE heifers were less (PRE|NoCIDR: 29.2% and PRE|CIDR: 30.4%) than that of PUB (PUB|NoCIDR: 50.7% and PUB|CIDR: 42.2%). Less PRE (42.5%) than PUB animals (69.7%) were AI at estrus, and heifers showing estrus had a higher P/AI (52.8% vs. 18.7%). In conclusion, induction is not required when the subsequent synchronization protocol for AI contains progesterone. Induction hastened puberty attainment but failed to improve estrus response and fertility to the synchronization protocol.